Synthesis and Evaluation of New Phthalazine Urea and Thiourea Derivatives as Carbonic Anhydrase Inhibitors - Nurcan Berber; Mustafa Arslan; Emre Yavuz; Cigdem Bilen; Nahit Gencer (Journal of Chemistry)
A new series of phthalazine substituted urea and thiourea derivatives were synthesized, and their inhibitory effects on the activity of purified human carbonic anhydrases (hCAs I and II) were evaluated. 2H-Indazolo[2,1-b]phthalazine-trione derivative (1) was prepared with 4-nitrobenzaldehyde, dimedone, and phthalhydrazide in the presence of TFA in DMF, and nitro group was reduced to amine derivative (2) with SnCl2·2H2O. The compound was reacted with isocyanates and isothiocyanates to get the final products (3a–p). The results showed that all the synthesized compounds inhibited the CA isoenzymes activity. 3a (IC50 = 6.40 µM for hCA I and 6.13 µM for hCA II) has the most inhibitory effect. The synthesized compounds are very bulky to be able to bind near the zinc ion, and they much more probably bind as the coumarin derivatives.